Publicity, punishment and protection: the role(s) of adverse publicity in consumer policy - Cartwright, Peter (Wiley, 2012)
This paper argues that adverse publicity can fulfil two crucial roles in consumer protection law and policy. First, it can operate as an effective regulatory sanction in its own right; secondly it can play a vital role in helping consumers to exert market discipline by making informed choices about suppliers. However, there are significant risks to using adverse publicity to achieve these ends and it is imperative that any regulatory regime addresses these. Studying this topic now is particularly important for three main reasons. First, there has been widespread recognition that the regulatory offence, typically backed up with fines, is not the most effective form of sanction. More flexible, targeted and responsive options are required. Secondly, there is now ample evidence that regulated information, for example in the form of mandatory disclosure, frequently fails to help consumers to make fully informed choices. Finally, there are some highly significant very recent examples of enforcers using publicity in ways that can be viewed both as a sanction and as an information tool. The need to sanction responsively and to bolster consumer sovereignty demonstrates the potential for adverse publicity as a tool of consumer protection policy.